MALT1-Ubiquitination Triggers Non-Genomic NF-κB/IKK Signaling upon Platelet Activation - Karim, Zubair A. (PLoS One, 2015)
We have recently shown that IKK complex plays an important non-genomic role in platelet function, i.e., regulates SNARE machinery-dependent membrane fusion. In this connection, it is well known that MALT1, whose activity is modulated by proteasome, plays an important role in the regulation of IKK complex. Therefore, the present studies investigated the mechanism by which IKK signaling is regulated in the context of the platelet proteasome. It was found that platelets express a functional proteasome, and form CARMA/MALT1/Bcl10 (CBM) complex when activated. Using a pharmacological inhibitor, the proteasome was found to regulate platelet function (aggregation, integrin activation, secretion, phosphatidylserine exposure and changes in intracellular calcium). It was also found to regulate thrombogenesis and physiologic hemostasis. We also observed, upon platelet activation, that MALT1 is ubiquitinated, and this coincides with the activation of the IKK/NF-κB-signaling pathway. Finally, we observed that the proteasome inhibitor blocks CBM complex formation and the interaction of IKKγ and MALT1; abrogates SNARE formation, and the association of MALT1 with TAK1 and TAB2, which are upstream of the CBM complex. Thus, our data demonstrate that MALT1 ubiquitination is critical for the engagement of CBM and IKK complexes, thereby directing platelet signals to the NF-κB pathway.